Effects of diverse resistance training modalities on performance measures in athletes: a network meta-analysis - Zhu, Zhipeng; Wu, Haowen; Li, Longpeng; Jia, Mingyuan; Li, Dong (Frontiers in Physiology, 2024)
Background: Jumping ability is one of the necessary qualities for athletes. Previous studies have shown that plyometric training and complex training including plyometrics can improve athletes' jumping ability. With the emergence of various types of complex training, there is uncertainty about which training method has the best effect. This study conducted a meta-analysis of randomized controlled trials of plyometric-related training on athletes ' jumping ability, to provide some reference for coaches to design training plans.We systematically searched 3 databases (PubMed, Web of Science, and Scopus) up to July 2023 to identify randomized controlled trials investigating plyometrics related training in athletes. The two researchers conducted literature screening, extraction and quality assessment independently. We performed a network meta-analysis using Stata 16. Results: We analyzed 83 studies and found that complex training, which includes high-intensity intervals and plyometric exercises, was the most effective method for improving squat jumps (SURCA=96%). In the case of countermovement jumps a combination of electrostimulation and plyometric training yielded the best results (SURCA=97.6%). Weightlifting training proved to be the most effective for the standing long jump (SURCA=81.4%), while strength training was found to be the most effective for the five bounces test (SURCA=87.3%).Our current study shows that complex training performs more efficient overall in plyometric-related training. However, there are different individual differences in the effects of different training on different indicators (e.g., CMJ, SJ, SLJ, 5BT) of athletes. Therefore, in order to ensure that the most appropriate training is selected, it is crucial to accurately assess the physical condition of each athlete before implementation.Trial registration: Registration and protocol CRD42023456402.